Effects of creatine supplementation on exercise performance - Demant, T. W.; Rhodes, E. C. (Sports Medicine, 1999)
Although creatine concentration (Cr) is greater in fast twitch muscle fibres, slow twitch fibres have a greater resynthesis capability due to their increased aerobic capacity. There appears to be no significant difference between males and females in Cr, and training does not appear to effect Cr. The 4 roles in which creatine is involved during performance are temporal energy buffering, spatial energy buffering, proton buffering and glycolysis regulation. Creatine supplementation of 20g per day for at least 3 days has resulted in significant increases in total Cr for some individuals but not others, suggesting that there are 'responders' and 'nonresponders'. These increases in total concentration among responders is greatest in individuals who have the lowest initial total Cr, such as vegetarians. Increased concentrations of both Cr free and CP are believed to aid performance by providing more short term energy, as well as increase the rate of resynthesis during rest intervals. Creatine supplementation does not appear to aid endurance and incremental type exercises, and may even be detrimental. Studies investigating the effects of creatine supplementation on short term, high intensity exercises have reported equivocal results, with approximately equal numbers reporting significant and nonsignificant results. The only side effect associated with creatine supplementation appears to be a small increase in body mass, which is due to either water retention or increased protein synthesis.